Building interactive worlds in 3D : virtual sets and pre-visualization for games, film, and the Web - Gauthier, Jean-Marc, 1960- (Elsevier/Focal Press, 2005)
Jean-Marc Gauthier offers a tutorial-based, step-by-step text containing sophisticated, professional-level tips and tricks to help designers, programmers and 3D artists create interactive environments and virtual sets relevant to film and computer games direction, and animation and web development.